Rapidness Characteristics of Ultrasonic Wave Propagation on Eggs Using HC-SR04 Module - Y E Putra; Sri Ratna Sulistiyanti; FX Arinto Setyawan; A S Samosir (Journal of Engineering and Scientific Research, 2021)
Fertility rate is one of the main factors of the success of an egg in order to hatch properly. The process of egg fertility detection is currently visually based, using manual methods (by carrying eggs one by one). This takes time and cost so that it will affect the production of poultry cultivation. This study aims to find out the characteristics of rapid propagation of ultrasonic waves in eggs. Information regarding the characteristics of rapid wave propagation is very important in the process of evaluating and testing the quality of eggs because the rapid propagation of the wave reflects the quality of the eggs that are generally done destructively.  This research is expected to be preliminary information in developing rapid and objective non-destructive technology for determining the fertility of poultry eggs using ultrasonic waves. The study reported the results of rapid measurements of ultrasonic wave propagation propagated on different types of eggs. This study used three types of eggs, namely poultry-chicken eggs, organic-chickens and ducks. Methods in the process of determining the characteristics of each egg using ultrasonic waves. Ultrasonic waves are waves that can propagate on certain objects, materials and components. The HC-SR04 module is used as an ultrasonic wave transmitter and receiver medium. Ultrasonic waves of 40 Khz are propagated to the surface of the egg and received by a receiver transducer placed facing each other. The distance between the egg and the HC-SR04 module is 5 cm and 10 cm. Distance and length of propagation time parameters are used as information to generate egg wave propagation speed values. The test process was carried out on 10 eggs, from each type. The observed age of the egg sample was 5 and 14 days. Based on the results of testing and calculations provide results that duck eggs have the highest speed value, while chicken eggs are the lowest. Keywords: Egg, Ultrasonic Waves, HC-SR04, Propagation Speed